Fatigue-Sensitive Afferents Inhibit Extensor but Not Flexor Motoneurons in Humans - Martin, Peter G. (J Neurosci, 2006)
The role of group III and IV muscle afferents in controlling the output from human muscles is poorly understood. We investigated the effects of these afferents from homonymous or antagonist muscles on motoneuron pools innervating extensor and flexor muscles of the elbow. In study 1, subjects (n = 8) performed brief maximal voluntary contractions (MVCs) of elbow extensors before and after a 2 min MVC of the extensors. During MVCs, electromyographic responses from triceps were evoked by stimulation of the corticospinal tracts [cervicomedullary motor evoked potentials (CMEPs)]. The same subjects repeated the protocol, but input from fatigue-sensitive afferents was prolonged after the fatiguing contraction by maintained muscle ischemia. In study 2, CMEPs were evoked in triceps during brief extensor MVCs before and after a 2 min sustained flexor MVC (n = 7) or in biceps during brief flexor MVCs before and after a sustained extensor MVC (n = 7). Again, ischemia was maintained after the sustained contractions. During sustained MVCs of the extensors, CMEPs in triceps decreased by ∼35%. Without muscle ischemia, CMEPs recovered within 15 s, but with maintained ischemia, they remained depressed (by ∼28%; p < 0.001). CMEPs in triceps were also depressed (by ∼20%; p < 0.001) after fatiguing flexor contractions, whereas CMEPs in biceps were facilitated (by ∼25%; p < 0.001) after fatiguing extensor contractions. During fatigue, inputs from group III and IV muscle afferents from homonymous or antagonist muscles depress extensor motoneurons but facilitate flexor motoneurons. The more pronounced inhibitory influence of these afferents on extensors suggests that these muscles may require greater cortical drive to generate force during fatigue.